EFFECT OF DIFFERENT ADDITION OF FISH BONE FLOUR (Clarias gariepinus, Pangasius djambal, and Paraplotosus albilabris) ON THE COOKIES QUALITY - Sari, Cindy kemala; Dewita, Dewita; Sumarto, Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This study aimed to determine the effect of different addition of fish(Clarias gariepinus, Pangasius djambal, and Paraplotosus albilabris) bone flour on the cookies quality and obtain the best formulation of cookies with addition differentfish bone flour. The experimental method with a non-factorial Completely Randomized Design was used in this research with 4 levels of treatment: cookies without addition of fish bone flour (CT0), cookies with addition 8gr of Clarias gariepinus bone flour (CT1), cookies with addition 8gr of Pangasius djambal bone flour (CT2), cookies with addition 8 gr of Paraplotosus albilabris bone flour (CT3). The parameters measured in this study were organoleptic test (appearance, odor, taste, texture),proximate analysis (water, protein, fat, ash and calcium content). The results showed that the addition 8 gr of Pangasius djambal bone flourwas the best treatment, whereas the appearance was brown, attractive, whole and neat, odor was distinctive smelling cookies, fragrant and slightly smelling fish, taste was good, savory and a little taste of fish, texture was dry, solid, compact and crunchy. Based on the best proximate analysis that the addiiton 8 gr of Paraplotosus albilabrisbone flour was the best treatment (CT3), where as the value of water, protein, fat, ash, carbohydrate and calcium content was 5.71%, 25.5%, 1.7%, 2.38%, 66.66%, 1.28%, respectively.Keywords: Clarias gariepinus, Cookies, Fish Bone Flour,Pangasius djambal, Paraplotosusalbilabris